A Comprehensive Analysis of METTL1 to Immunity and Stemness in Pan-Cancer - Gao, Zijie; Xu, Jianye; Zhang, Zongpu; Fan, Yang; Xue, Hao; Guo, Xing; Deng, Lin; Wang, Shaobo; Zhao, Rongrong; Zhang, Ping; Li, Gang (Frontiers in Immunology, 2022)
Background: Previous studies have reported the effect of N7-methylguanosine (m7G) regulator methyltransferase like-1 protein (METTL1) in tumor initiation, metastasis, and chemosensitivity. However, the relationship between METTL1 and cancer immune infiltration is not yet validated and the prognostic role of METTL1 in pan-cancer remains elusive. Methods: The gene expression data and clinical characteristics of 33 cancers were retrieved from University of California Santa Cruz Xena database. The immunotherapeutic cohorts included IMvigor210, GSE67501, and GSE78220. Clinical parameters, including patient age, gender, survival, tumor stage, and treatment response were analyzed to assess the prognostic value of METTL1. The METTL1 activity was generated by single sample gene set enrichment analysis and used to evaluate the difference between the METTL1 transcriptome and expression level. The one-class logistic regression algorithm was used to calculate the stemness indices based on transcriptomics and methylation data of pan-cancer and pluripotent stem cells. To better understand the role of METTL1 in cancer immunotherapy, the correlation between METTL1 and tumor microenvironment, as well as its relation to immune processes, such as immune cell infiltration, immune inhibitors and stimulators, and the major histocompatibility complex were analyzed. Furthermore, the correlation between METTL1 and three immunotherapeutic biomarkers was investigated. Finally, spearman correlation analysis was used to calculate the correlation between drug sensitivity and METTL1 expression. Results: Although METTL1 was not closely associated with age, gender, or tumor stage in any of the studied human cancers, it exhibited potential prognostic value for predicting patient survival. Consistency has been observed between METTL1 activity and expression in some cancers (8/33). Generally, high METTL1 expression was significantly related to tumor progression-relevant pathways. Moreover, METTL1 presented a robust correlation with immune cell infiltration, immune modulators, immunotherapeutic markers, and stemness. The METTL1 expression in the response group were significantly higher than those in the no/limited response group in anti-PD-L1 cohort. Further analysis indicated that patients with higher METTL1 expression may benefit more from drugs targeting the chromatin histone methylation, ERK-MAPK and WNT signaling pathways. Conclusion: This research investigated the immunotherapeutic value of METTL1 in 33 human cancers, providing evidence regarding the function of METTL1 and its role in clinical treatment.